ÆLas mujeres se tomaron las imprentas de Gurropin! : debates alrededor de la ciudadanía femenina en las revistas Cromos y Mundo Femenino durante el gobierno militar de Gustavo Rojas Pinilla (1954-1956) (2017)
"The work develops the way in which two newspapers: Cromos and Mundo Femenino represent women, in the mid-twentieth century, in order to consolidate a discourse that establishes female citizenship beyond the suffragist subject. In this sense, we analyze the representations of women in the labor struggles and in the practices of consumption and fashion through articles, chronicles and advertising guidelines".-- Tomado del Formato de Documento de Grado